Transformasi Sosial dan Hubungannya dengan Pembagian Harta Warisan Menurut Perspektif Hukum Islam - Ritonga, Raja; Aulia Rezi; Asril Fauzi (Sekolah Tinggi Agama Islam Negeri Majene, 2023)
Islamic teachings are built on the foundation of maslahah and anticipate mafsadah. Therefore, changes to a law can occur along with certain conditions and time. This article explains the relationship between social transformation and the distribution of inheritance from an Islamic legal perspective. This also explains how social transformation in the community influences the distribution of inheritance. This research is library research, in collecting data a search was carried out on a number of books, articles and other scientific works that were relevant to the research theme. Based on this study, social transformation can have an impact on the distribution of inheritance, especially in terms of implementing wasiyyat al-wajibah. So, these laws can change due to al-maslahah al-murlahah, whereas, some qath'i (certain) laws regarding the distribution of inheritance will not change even though they are influenced by changing times and social and other influences.